Association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and metabolic dysfunction-associated steatotic liver disease - Yang, Dandan; Dai, Hongsheng; Wang, Yulu; Zhang, Jiayi; Wei, Min; Shan, Ming; Zhang, Xiaoqian (Frontiers in Nutrition, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) is one of the most widespread chronic liver diseases and a serious global public health problem. Further research to identify novel risk factors associated with MASLD is urgently needed. The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) was identified as a novel lipid marker. The objective of this research was to assess the association between NHHR and MASLD in adults.MethodsThis cross-sectional study utilized data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES). MASLD was diagnosed in accordance with controlled attenuation parameter scores and a combination of cardiometabolic risk factors. Multivariate logistic regression analyses, in conjunction with the restricted cubic spline method, were employed to investigate the association between NHHR and MASLD risk. Furthermore, subgroup and interaction analyses were conducted.ResultsThis study included 5,269 individuals, with 2,031 individuals diagnosed with MASLD and 3,238 without MASLD. Logistic regression analyses revealed a significant positive correlation between NHHR and MASLD. After the confounding factors were adjusted, each unit rise in NHHR was correlated with a 39% higher probability of MASLD (OR = 1.39, 95% CI: 1.13–1.69). Subgroup and interaction analyses revealed that the positive correlation between NHHR and MASLD held steady regardless of age, gender, race, poverty-to-income ratio, education level, physical activity, body mass index, diabetes, hypertension, dyslipidemia and smoking status (P for interaction >0.05). In addition, a non-linear relationship with an S-shaped manner between NHHR and MASLD was found, with an inflection point at 1.59.ConclusionOur findings imply that an increasing trend in NHHR is associated with a greater risk of MASLD development. NHHR has the potential to function as an indicator for estimating the likelihood of developing MASLD.